Interculturality in the Practice of Experiential Rural Tourism in a Community in the Peruvian Andes - Mamani-Flores, Adderly; Calatayud-Mendoza, Alfredo Pelayo; Paredes-Calatayud, Edith Fernanda; Vizcarra-Pinto, Florentino; Cotrado-Lupo, Sheylla Lía; Maquera-Maquera, Yuselino; Incacutipa-Limachi, Duverly Joao (Journal of Ecohumanism, 2024)
The practice of experiential rural tourism involves the active participation of the local population, promoting cultural exchange between visitors and residents, generating intercultural relations that occur in the town of Ccotos located in the district of Capachica, in the region of Puno. The objective of the research was to analyze the intercultural relationships that are established between local inhabitants and tourists within the framework of the development and experiences of the practice of experiential rural tourism. The elements studied include communication, mutual respect, socio-economic growth, cultural authenticity, shared cultural customs, reciprocity, appreciation of cultural identity and environment; in addition to the perceptions and experiences of visitors and local inhabitants, as well as the challenges and possibilities that emerge from these interactions. The methodology used the qualitative approach and the techniques applied were in-depth interviews with the local population and tourists, direct observation of the practice of this activity and content analysis. The results revealed the complexity of intercultural relations in experiential rural tourism, highlighting the importance of a participatory and collaborative approach to guarantee equity, mutual respect and long-term sustainability that are generated in the meaningful interactions that occur between tourists and residents, facilitating the exchange of knowledge and mutual understanding becoming consolidated as intercultural relations.